Reproductive allometry and plasticity in relation to plant population density in soybean [(Glycine max L.) Merrill.] - El-Zeadani, Hassan Hamad Hassan (2015)
The vegetative and reproductive stages during plant growth are strongly interdependent and ultimately influence the potential yield. The biomass produced by plant during the early part of its life cycle are eventually allocated to various vegetative and reproductive structures and functional plant processes. From an agronomic perspective, biomass quantification to different plant organs especially to the economic yield based on allometric and plasticity analyses are limited. Thus, the general objective of this study was to evaluate the use of allometry and plasticity approaches in comparing several soybean varieties in relation to changes in plant population densities especially under the tropical growing environment. The specific objectives were: (i) to determine the effect of plant population density of selected vegetable- and grain-type varieties of soybean on changes of growth rates and seed fill duration at specific reproductive growth stages and the relationships of individual seed growth rate (SGRi) and seed filling period (SFP) with yield components, (ii) toquantify allometric changes based on relative growth rate of leaf and seed mass, and source-sink relationship due to plant population pressures at specific reproductive growth stages, and (iii) to determine yield plasticity responses to plant density variations based on individual plant and per area basis, and the use of plasticity for designing the optimal field planting density. In the first experiment (2010), three soybean varieties [AGS 190 (vegetable-type), Palmetto and Deing (grain-types)] were grown at 20, 30, and 40 plants m-2. The second experiment (2011), AGS190 and grain-types of Argomolio and Willis were grown at 20, 30, and 50 plants m-2. At 20, 30, and 40 or 50plants m-2 are considered as low (L), normal (N), and high planting density (H), respectively. The field experimental design in both years was randomized complete block design (RCBD) with three replications. Plant density did not affect the SGRi or SFP, but they differ among varieties during different reproductive growth stages. Dry matter accumulation in the seed was highest during reproductive growth stages from full size seed to physiological maturity stage (R6 to R7, respectively). This period of seed growth and development had the highest SGRi and SFP. Increased plant density had decreased seed number of individual plant. Seed number per plant adjustments indicated the stability of individual final seed size within variety that was insensitive to the changes in plant density. Both SGRi and SFP were correlated negatively with seed number per plant and positively with final seed size. In this study (under humid tropical growing conditions) the selected vegetable- and grain-type soybeans could be grown successfully even with maximum daily temperature ˃ 32˚C, and the seed number, seed weight per plant, and number of plants per area were important features to determine yield potential. The source-sink relationship of leaf and seed mass per plant with the consideration of time were analyzed allometrically by taking the ratio of respective relative growth rate of leaves (RGRl) to seeds (RGRs) with a model where α = allometry. The derived ‘α’ values explain three types of biomass allocation to seeds. At α > 0 allometry zone, the leaves daily current photoassimilate was used for further leaf growth while partitioning some for seed development. When at α = 0 zone, it was a point in which all current photoassimilate in green leaves was partitioned to seed development, and it corresponds to the beginning of linear phase of seed growth. It occurred at the beginning of R6 for vegetable-type of AGS190 and the beginning of R5 for the grain-types of Deing, Palmetto, Argomolio, and Willis. In the zone of α < 0, the leaves begin to senesce and the increase in seed size that primarily due to mobilization current and stored assimilates from vegetative organs and also current photosynthetic produced by the green tissues of reproductive organ. Related to allometry analysis, the beginning of the effective seed filling period (ESFP) was determined based on the intersection point of the proportionate leaf RGR and seed mass to their respective predicted maximum values that produced by the curves of indicates the predicted values of the leaf RGR and seed mass that firstly converted to their proportionate values based on their maximum predicted values, and t is days after planting. The ESFP that generated in this study is an alternative to effective filling period (EFP) method with an additional feature that simultaneously includes vegetative and reproductive growth consideration. The method of ESFP was found quantitatively and physiologically reliable in the five tested soybean varieties for two growing seasons. Average overall densities, the ESFP and EFP for all varieties studied were shorter or similar to the duration of morphological stages of beginning seed (R5) to physiological maturity (R7). Plasticity based on per plant and per area basis were indexed as pt and Pt, respectively. Varieties tested showed high plasticity (pt) in seed number per plant for density setting of L-H than that of L-N where L, N, and H were the low, normal, and high densities, respectively. This result indicated that seed number per plant was gradually reduced with increasing plant density. Genetically, the range of plasticity was slightly less for the large seeded vegetable-type variety (AGS190) than those of the small seeded grain-type varieties (Argomolio, Palmetto, Willis and Deing) grown in Malaysia tropical conditions. The plasticity of seed number based on per area basis (Pt) was predicted by new model There were three types of plasticity in seed m-2 across plant densities pressure; positive, negative and no phenotypic plasticities. The curve that started with a positive plasticity with increasing plant density had optimum planting density related design at its lower density (20 plants m-2) which was observed in AGS190 and Willis. A trend that started with a negative plasticity with increasing density, the optimal planting density occurred when Pt = 0. At this plasticity, the estimated optimum planting densities for Deing, Palmetto, and Argomolio ranged between22 - 29 plants m-2 to achieve maximum seed number m-2. The optimum yield per area occurred at low to normal density range. Per area plasticity is more practical than the per plant basis plasticity when describing the maximum yield for the designing of planting densities in soybean cultivation in tropical environments. The study had successfully used the allometry and plasticity in describing the agronomic and physiological indicators in growing soybean under the tropical condition. The physiologists, breeders and agronomists should exploit on the allometry of RGR of leaves over seeds (α = 0), per plant plasticity (pt= 0), and per area plasticity (Pt = 0 or the first appearing of Pt when Pt start with positive value in Pt versus density curve), respectively in developing and expending soybean varieties that could be successfully grown under humid tropical environments.